2021
DOI: 10.1109/access.2021.3062978
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Ambulatory Assessment of 3D Knee Angle Using Novel Inertial Sensor-Based Technique

Abstract: Three-dimensional (3D) knee angle measurement is one of the key measures in human gait analysis. Inertial sensor capable of measuring joint motion under unconstrained conditions is a practical tool for clinical evaluation and rehabilitation. An inertial measurement unit (IMU) consisting of accelerometer and gyroscope allows orientation measurement in 3D with an additional sensor (i.e., magnetometer). However, ferromagnetic interference negatively affects the performance of magnetometer and thus reduces measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Sensors 2023, 23, 5463 2 of 12 joint angles using inertial sensors, NARX can avoid the influence of magnetometers, accurately estimate 3D knee joint angles and measure 3D joint angles in the long term [17]. In the same year, a full-body wireless wearable motion-sensing system was reported by Lee et al to study the motion of human lower limbs and arms, which can reconstruct simple 3D human body models in real-time using quaternion data measured by sensors [18].…”
Section: Et Al Demonstrated That When Measuringmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensors 2023, 23, 5463 2 of 12 joint angles using inertial sensors, NARX can avoid the influence of magnetometers, accurately estimate 3D knee joint angles and measure 3D joint angles in the long term [17]. In the same year, a full-body wireless wearable motion-sensing system was reported by Lee et al to study the motion of human lower limbs and arms, which can reconstruct simple 3D human body models in real-time using quaternion data measured by sensors [18].…”
Section: Et Al Demonstrated That When Measuringmentioning
confidence: 99%
“…Figueiredo et al proposed a wearable inertial sensor system for real-time detection of 3D angular velocity and 3D acceleration for up to six lower limbs and trunk segments, and sagittal joint angle for up to six lower limb joints [ 16 ], but they do not have a 3D model which was used to show the human gait. Tham et al demonstrated that when measuring joint angles using inertial sensors, NARX can avoid the influence of magnetometers, accurately estimate 3D knee joint angles and measure 3D joint angles in the long term [ 17 ]. In the same year, a full-body wireless wearable motion-sensing system was reported by Lee et al to study the motion of human lower limbs and arms, which can reconstruct simple 3D human body models in real-time using quaternion data measured by sensors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other RNNs are also used to estimate the joints orientation. To estimate the joint angles from gyroscopes and accelerometers, [54] proposes a NARX; and [134] also includes the magnetometer data with NARX and LSTMs.…”
Section: Adopted Algorithmsmentioning
confidence: 99%
“…the joint or segment orientation or location. In this review, we found 26 works that use reference data, that can be obtained from a stereophotogrammetric system (17/26) [21], [27], [34], [49], [53], [54], [56], [58], [68], [69], [86], [90], [91], [103], [111], [114], [115], electro-goniometer and encoders (2/26) [71], [84] or inertial sensors (7/26) [29], [100], [109], [134], [147], [148], [155]. Fig.…”
Section: Adopted Algorithmsmentioning
confidence: 99%
“…The estimated variables can be used to extract gait parameters of interest. For instance, IMU data has been used to estimate gait events (Pacini Panebianco et al, 2018), walking speed (Sabatini et al, 2005), joint angles (Muro-de-la-Herran et al, 2014;Tham et al, 2021), foot pose and trajectory (Okkalidis et al, 2020a) etc. We also employ this 'physical model' approach in Chapters VI -X for estimating ground reaction forces, Centre of Mass (CoM) velocity, and relative movement of feet and CoM.…”
Section: Portable Gait Lab (Pgl)mentioning
confidence: 99%